2021
DOI: 10.1001/jamainternmed.2021.6272
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cycling With All-Cause and Cardiovascular Disease Mortality Among Persons With Diabetes—Reply

Abstract: To the Editor We read with great interest the Original Investigation recently published in this journal by Dr Ried-Larsen and colleagues. 1 The authors reported decreased mortality from all causes and from cardiovascular diseases associated with cycling in adults with diabetes. The large sample size and the robust analyses are strengths of the study. However, it is surprising that the reported association between cycling and mortality was independent of practicing other types of physical activity. An almost l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The data in the report by Ried-Larsen and colleagues add to previous studies showing benefits of cycling compared with other physical activity. A previous large Danish study published in 2000 showed significant health benefits of cycling to work, such as a 40% decreased risk of mortality after multivariate adjustment, including leisure-time physical activity.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The data in the report by Ried-Larsen and colleagues add to previous studies showing benefits of cycling compared with other physical activity. A previous large Danish study published in 2000 showed significant health benefits of cycling to work, such as a 40% decreased risk of mortality after multivariate adjustment, including leisure-time physical activity.…”
mentioning
confidence: 70%
“…A previous large Danish study published in 2000 showed significant health benefits of cycling to work, such as a 40% decreased risk of mortality after multivariate adjustment, including leisure-time physical activity. The analysis from Ried-Larsen and colleagues strengthens the epidemiologic data on cycling and strongly suggests that it may contribute directly to longer and healthier lives. As avid and/or aspiring cyclists ourselves, we are sold on the mental and physical benefits of getting to work and seeing the world on 2 wheels, self-propelled, and think it is well worth a try.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In terms of morbidity, we showed that the disease most frequently prevented were diabetes and cardio-vascular diseases. Previous studies reported that cycling also contributes to reducing mortality among adults with diabetes 35 , making it a relevant intervention for both primary and secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of morbidity, we showed that the disease most frequently prevented were diabetes and cardio-vascular diseases. Previous studies reported that cycling also contributes to reducing mortality among adults with diabetes 41 , making it a relevant intervention for both primary and secondary prevention. Due to the lack of reliable medical costs data, our estimate disregarded some diseases which were considered in some previous HIA of cycling, especially depression 25,42 .…”
Section: Discussionmentioning
confidence: 99%